Penguatan Literasi Sebagai Bagian Gerakan Literasi Perpustakaan Masjid Pada Masjid Haramain Desa Tratak Lombok Tengah - Silka Yuanti Draditaswari; Hairul Hidayah; Baiq Rofina Arvy; Anjar Aprillia Kristanti; Liska Novianti Paramitaswari (Yayasan Tajuk Indonesia, 2024)
The low reading interest in Indonesia presents a significant challenge, particularly among children. The National Literacy Movement (GLN) initiated by the goverment, aims to foster a culutre of literacy across various domains, including mosques. Mosques, as centers of Islamic community activites, hold substantial potential to support literacy movements through their libraries. This community engagement program was conducted at the Haramain Mosque Library in Tratak Village, Central Lombok, which demonstrates considerable potential to become a hub for childrens literacy. Initial observations revealed limited book collections and a lack of literacy activites in the library. The program aimed to establish structured literacy development by providing engaging reading materials, organizing the library environment, involving literacy ambassadors, and implementing a 15-minute reading program before Qur’anic lessons. The program outcomes showed an increase in children’s reading interest, despite challeenges such as prioritizing Qur’anic lessons. The program outcomes showed ann increase in children’s reading interest, despite challenges such as prioritizing Qur’anic learning time. This initiative had a positive impact on fostering reading habits and enhancing the mosque’s role as a community literacy center. The sustainability of the literacy program requires improvement htrough reading materials, optimizing technology, and fostering collaboration with relevant stakeholders.